121k views
5 votes
Name a point on this line.

y - 8 = -7(x + 1)

Question 4 options:

(-1, 8)


(-8, 1)


(8, -1)


(1, -8)

User Ziga Petek
by
5.4k points

1 Answer

5 votes

Answer: y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x + y - 8 = -7(x +

Step-by-step explanation: 8, -1)

User Juan Jimenez
by
4.8k points